2010
DOI: 10.1007/s11270-009-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of Infiltration Trench for Nonpoint Source Pollution Control

Abstract: Nonpoint source pollution management initiated by the Ministry of Environment (MOE) in Korea resulted to the construction of 25 pilot facilities termed Best Management Practices (BMPs) until 2005. The national nonpoint sources control projects were employed to fulfill the Total Maximum Daily Load programs. The long-term monitoring being conducted at the sites which began in 2006 is providing detailed insight into the performance of the BMPs. The experience and performance data will be used to better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…This is consistent with other studies, including Brezonik and Stadelmann (2002) who found contaminant fluxes to be positively correlated with TR and RI, but negatively correlated with DAT. Findings by Maniquiz et al (2010) from Yongin City, Korea, are consistent with these results while those by Wang et al (2013) show an opposite trend. In contrast to EMC values, conventional rainfall parameters TR and VD should be good predictors of EF values in a combined system, while for the storm sewer system, VD is the dominant variable (Table 7).…”
Section: Correlation Between Emc and Rainfall Variablessupporting
confidence: 73%
See 2 more Smart Citations
“…This is consistent with other studies, including Brezonik and Stadelmann (2002) who found contaminant fluxes to be positively correlated with TR and RI, but negatively correlated with DAT. Findings by Maniquiz et al (2010) from Yongin City, Korea, are consistent with these results while those by Wang et al (2013) show an opposite trend. In contrast to EMC values, conventional rainfall parameters TR and VD should be good predictors of EF values in a combined system, while for the storm sewer system, VD is the dominant variable (Table 7).…”
Section: Correlation Between Emc and Rainfall Variablessupporting
confidence: 73%
“…Aside from the October 6 event, which was preceded by a 14-days stretch of dry weather at both sites, the durations of dry periods preceding all the other events falls are within the summer average, which is generally shorter than a week for the region and period of interest. This may serve to restrict the accumulation of pollutants on developed surfaces, thus limiting pollutant remobilization by runoff (Maniquiz et al, 2010). CSO: combined sewer overflow; CV: coefficient of variation; RD: rainfall duration; TR: total rainfall; RI: rainfall intensity in 5 min; VD: volume discharged; DAT: dry antecedent time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanization has adversely affected the quantity and quality of urban water resources [1,2] because of increased impervious surfaces, compaction of soils, and modifications to vegetation [3,4], which has reduced infiltration rates and increased stormwater runoff [5]. Impervious surfaces like pavement, rooftops, and parking lots increase stormwater runoff volume and contaminant loads in stormwater.…”
Section: Introductionmentioning
confidence: 99%
“…The experience and performance data collected will be used to better understand and implement similar BMPs in the future as well as to assist the MOE in developing and improving the design and maintenance guidelines of BMPs (Maniquiz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%